Effect of gradual reduction of graphene oxide on the CO tolerance of supported platinum nanoparticles. (January 2017) - Abidat, I.; Morais, C.; Pronier, S.; Guignard, N.; Comparot, J.D.; Canaff, C.; Napporn, T.W.; Habrioux, A.; Mamede, A.-S.; Lamonier, J.-F.; Kokoh, K.B.
Abstract: Gradually reduced graphene oxide materials were successfully synthesized by performing successive chemical treatments on graphite oxide synthesized using Hummers' method. These materials were deeply characterized using complementary spectroscopic techniques (X-ray induced photoelectron spectroscopy, UV- spectroscopy, Fourier transform infrared spectroscopy and Raman spectroscopy). It was shown that reduction processes allow removing oxygenated functional groups. Nevertheless, defects in the carbon structure materials formed subsequently to the oxidation step remain after such reducing treatments. CO stripping coupled with in-situ Fourier transform infrared spectroscopy measurements revealed that the reduction extent of the carbon-based materials affects the electron density on Pt thus engendering modifications in the adsorption strength of CO molecule. Graphical abstract: